A provider survey of cystic fibrosis related diabetes screening and management practices at North American CF centers - Hicks, Rebecca; Ode, Katie Larson; Vigers, Tim; Chan, Christine L. (Frontiers in Endocrinology, 2023)
Background: Cystic Fibrosis Foundation (CFF) Guidelines recommend annual screening for cystic fibrosis related diabetes (CFRD) with an oral glucose tolerance test (OGTT). However, screening rates remain consistently low. We conducted surveys of 1) US CF center directors and 2) Endocrinologists affiliated with the CFF-sponsored EnVision program to characterize CFRD screening practices, describe provider perceived barriers to screening, and identify strategies for improving screening. Methods: The surveys queried OGTT protocols, alternate screening strategies, and perceived barriers to screening. CF center characteristics and procedures for coordinating OGTTs were compared between centers achieving ≥50% versus <50% OGTT completion. Endocrinologists received additional questions regarding OGTT interpretation and management. Results: The survey response rate was 18% (51/290) from CF Centers and 63% (25/40) from Endocrinologists. The majority (57%) of CF centers utilized 2 OGTT timepoints (0,120 min). The majority (72%) of Endocrinologists utilized 3 timepoints (0,60,120 min). Four percent of CF centers and 8% of Endocrinologists utilized other timepoints. Forty-nine percent of CF centers reported ≥50% OGTT completion in the past year. Completion of ≥50% OGTT was 5 times more likely when patient reminders were consistently provided (p = 0.017). Both CF Centers and Endocrinologists employed alternative screening strategies including HbA1c (64%, 92%), fasting plasma glucose (49%, 67%), continuous glucose monitoring (30%, 58%), and home fingerstick monitoring (55%, 50%). Discussion: OGTT is the gold standard screening method for CFRD, but completion rates remain suboptimal, practice variation exists, and many providers utilize alternate screening strategies. Systematic reminders may improve completion rates. Studies to improve our approach to CFRD screening are urgently needed.